Conflicting identities : gender and ethnicity in the workplace - Piippola, Saila (Luleå tekniska universitet, Arbetsvetenskap, 2008)
In times of changes on the labor market turns our attention to what is called globalization and political intentions where equal opportunities to be self supporting calls for further interests. In the light of a liberal labour market discourse supporting anyone to cross national borders to work, there still exists a hidden agenda in which inclusion- and exclusion processes are articulated. In this process work migrated woman's working conditions have so far received little scholarly attention. The aim with this paper is to emphasize the work situation among nurses from northern Finland in northern Swedish hospitals. This qualitative data is based on a total of 40 semi-structured in-depth interviews collected during 2001-2002. This paper examines a work occupation traditionally dominated by women and the intersection where inclusion and exclusion processes are taking place. In summary crossing national borders is an option in contemporary society but can not bridge every difficulty encountered, such as language, lack of social network, family arrangements among single and coupled mothers. Godkänd; 2008; 20081112 (sapi)